Blocking porcine sialoadhesin improves extracorporeal porcine liver xenoperfusion with human blood. (4th July 2013) - Waldman, Joshua P.; Vogel, Thomas; Burlak, Christopher; Coussios, Constantin; Dominguez, Javier; Friend, Peter; Rees, Michael A.
Abstract: Background: Patients in fulminant hepatic failure currently do not have a temporary means of support while awaiting liver transplantation. A potential therapeutic approach for such patients is the use of extracorporeal perfusion with porcine livers as a form of "liver dialysis". During a 72‐h extracorporeal perfusion of porcine livers with human blood, porcine Kupffer cells bind to and phagocytose human red blood cells (hRBC) causing the hematocrit to decrease to 2.5% of the original value. Our laboratory has identified porcine sialoadhesin expressed on Kupffer cells as the lectin responsible for binding N‐acetylneuraminic acid on the surface of the hRBC. We evaluated whether blocking porcine sialoadhesin prevents the recognition and subsequent destruction of hRBCs seen during extracorporeal porcine liver xenoperfusion. Methods: Ex vivo studies were performed using wild type pig livers perfused with isolated hRBCs for 72‐h in the presence of an anti‐porcine sialoadhesin antibody or isotype control. Results: The addition of an anti‐porcine sialoadhesin antibody to an extracorporeal porcine liver xenoperfusion model reduces the loss of hRBC over a 72‐h period. Sustained liver function was demonstrated throughout the perfusion. Conclusions: This study illustrates the role of sialoadhesin in mediating the destruction of hRBCs in an extracorporeal porcine liver xenoperfusion model.